The Effectiveness of Using Wattpad Application to Increase Students’ Reading Skills - Arimbi, Gita Dwi; Daulay, Ernita (Jurnal Simki Pedagogia, 2024)
As technological advances develop in increasing students' interest in reading, the Wattpad social media application emerged as an effective media for providing learning materials, channeling creative ideas in writing, based on the complexity of the problem and the students’ apparent lack of interest in reading, technology utilization is required as a solution, including using Wattpad as a learning media. The purpose of this research is to ascertain whether using the Wattpad application to increase students' reading skills. In this research, researchers used quantitative methods with pre-experimental research in the form of one group pretest-posttest. The sample used consisted of 25 students from class VIII with purposive sampling type. Multiple-choice test is the method utilized to acquire the data. Based on the statistical statistics, the average pretest score was 59.00, while the average posttest score was 73.20. And to the paired sample t-test analysis results, Sig (2-tailed) < 0.05 (0.001 < 0.05), rejecting H0 and accepting Ha. This indicates that the Wattpad application is an effective media to increase students' reading skills. The use of wattpad is useful for increasing students' interest in reading through available technology and as an additional learning media so that students do not feel bored.